Printed Modified Bow-Tie Dipole Antenna for DVB/WLAN Applications - Ching-Chih Hung; Chia-Mei Peng; I-Fong Chen (International Journal of Antennas and Propagation)
A printed modified bow-tie dipole antenna which consists of asymmetric-feed and inserted slots is presented to apply to the DVB and WLAN systems. This antenna combines omnidirectional radiation pattern, broad bandwidth, and band rejection in an easy way to fabricate. Experimental results of the constructed prototype indicate that the VSWR 2.5 : 1 bandwidths achieve 166.7%, 28.57%, and 23.63% at 660 MHz, 2450 MHz, and 5500 MHz, respectively.